Little Geodetic Evidence for Localized Indian Subduction in the Pamir‐Hindu Kush of Central Asia. Issue 1 (3rd January 2019) - Perry, M.; Kakar, N.; Ischuk, A.; Metzger, S.; Bendick, R.; Molnar, P.; Mohadjer, S.
Abstract: Geodetically derived velocities from Central Asia show that Northern Afghanistan, the Tajik Pamir, and northwestern Pakistan all move northward with comparable large velocities toward Eurasia. Steep velocity gradients, hence high strain rates, occur only across the Main Pamir Fault zone and with lesser magnitude between the northernmost Hindu Kush and the south and southeast margins of the Tajik Depression. Localized shortening is not apparent on any active India‐Hindu Kush crustal boundary; hence, crustal convergence between India and Eurasia in Central Asia is absorbed primarily on the northern and western margins of the Pamir. This concentrated strain on the Pamir margins is consistent with one, geometrically complex, interface between subducting Asian lithosphere and the Pamir. That interface might curve westward such that the Hindu Kush seismic zone is a continuation of the Pamir seismic zone, or alternatively, Hindu Kush earthquakes might occur in convectively unstable mantle lithosphere mechanically detached from surface faults. Plain Language Summary: Using Global Positioning System (GPS) measurements of surface velocities, we find that much of the relative motion between India and Eurasia in Central Asia is accommodated on a single crustal boundary on the north side of the Pamir, wrapping around the eastern and southern margins of the Tajik Depression. Key Points: Crustal shortening is accommodated across the northern margins of the Pamir and Hindu Kush between NW Afghanistan and the Tajik Depression There is little geodetic evidence for localized crustal shortening on the south side of the Hindu Kush between Indian and Pamir crust Intermediate depth seismicity in the Hindu Kush cannot easily be linked to ongoing subduction of Indian lithosphere